Adaptive finite-time fault-tolerant controller for a class of uncertain MIMO nonlinear switched systems subject to output constraints and unknown input nonlinearities. (February 2020) - Moradvandi, Ali; Malek, Sayyed Alireza; Shahrokhi, Mohammad
Abstract: In this work, design of an adaptive finite-time fault-tolerant controller for a class of uncertain multi-input multi-output (MIMO) nonlinear switched systems with unmodeled dynamics subject to asymmetric time-varying output constraints and unknown faulty input nonlinearities has been addressed. The number of actuator faults can be infinite. In addition, the proposed control algorithm can cope with different unknown types of input nonlinearities namely, saturation, dead zone, backlash, and hysteresis. Actuator faults and input nonlinearities can be different in different modes. To estimate the system uncertainties, neural networks (NNs) have been employed and the unmodeled dynamics has been handled utilizing a dynamical signal. Finite-time convergence of the system outputs tracking errors to the neighborhood of the origin have been guaranteed, and the time-varying outputs constraints have been satisfied. By applying the backstepping control approach and using the common Lyapunov function (CLF) method, virtual and actual controllers and adaptive law for each subsystem have been constructed. The closed-loop stability and boundedness of all signals have been established. Through the simulation study, effectiveness of the proposed control scheme has been demonstrated.